Assessing the electricity consumption of outdoor lighting systems in the presence of automatic control: The OL-BAC factors method. (March 2020) - Bonomolo, Marina; Ferrari, Simone; Zizzo, Gaetano
Highlights: A new BAC factor method for outdoor lighting systems is proposed. The method improves the one suggested by EN 15232 for indoor applications. The method takes into account the latitude of the side and the consumption of the BAC system. The method is simple and easy to use. Abstract: Building automation systems are able to influence significantly buildings' energy performance. The BAC factors method, presented for the first time by the International Standard EN 15232, is the most used and simple instrument for evaluating the impact of such systems in terms of reduction of the electrical and thermal energy consumption of buildings services. Nevertheless, Standard EN 15232 does not take into consideration the automation of lighting systems serving buildings' external areas like passages, gardens, entrance walkways, etc. In some cases, such areas can be very extended and, as a consequence, responsible for a not negligible percentage of the overall electricity consumption. Taking this last consideration as a basis, in this paper, a method is proposed for the definition and the evaluation of a new BAC factor for outdoor lighting systems, named OL-BAC factor. The method can be considered complementary to the one proposed by the Standard EN 15232 for the indoor lighting energy consumption estimation and proposes some improvements in the implementation of the latter. In particular, in this paper, the OL-BAC factors are calculated showing the importance of two parameters that are not taken into account by the Standard EN 15232: the latitude of the installation site and the energy absorbed by the devices for the luminaires' automatic control.